Cognition and Experience of Social Participation in Stroke Survivors: a Meta-synthesis Based on Qualitative Studies - ZHAO Zhixin, MEI Yongxia, WANG Xiaoxuan, JIANG Hu, WANG Wenna, ZHANG Zhenxiang (Zhongguo quanke yixue)
Background As one of the important evaluation indicators of rehabilitation effect in stroke survivors, social participation has gradually attracted attention. Understanding the cognition and experience of social participation in stroke survivors is beneficial in helping stroke survivors recover quickly, return to families and reintegrate into society. However, the results of single qualitative studies may not be generalisable and representative. Objective To systematically review the qualitative studies on cognition and experience of social participation in stroke survivors by meta-synthesis methods, so as to provide a reference for further improving the rehabilitation effect of stroke survivors. Methods PubMed, Web of Science, Cochrane Library, Embase, PsycINFO, CINAHL, JBI evidence-based health care database, CNKI, Wanfang Data, VIP and CBM were searched by computers to screen qualitative studies on cognition and experience of social participation in stroke survivors from inception to November 2022. Pooled meta-integration method was used to perform the meta-synthesis of research themes, implications, classifications and so on. Results A total of 14 papers were included, involving 183 stroke survivors, and 26 findings were derived from meta-synthesis, which were summarized into 8 new categories, and 3 integrated findings were finally synthesized, including cognition and experience of social participation in stroke survivors, multiple social participation were limited in stroke survivors by multiple factors, multiple support for social participation was essential in stroke survivors. Conclusion Stroke survivors have new insights into social participation, and it is necessary to correct and eliminate the self-identification disorder and limiting factors of social participation, and focus on multi-party support of social participation in stroke survivors.